If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3)(x + -5) = 0 Reorder the terms: (-3 + x)(x + -5) = 0 Reorder the terms: (-3 + x)(-5 + x) = 0 Multiply (-3 + x) * (-5 + x) (-3(-5 + x) + x(-5 + x)) = 0 ((-5 * -3 + x * -3) + x(-5 + x)) = 0 ((15 + -3x) + x(-5 + x)) = 0 (15 + -3x + (-5 * x + x * x)) = 0 (15 + -3x + (-5x + x2)) = 0 Combine like terms: -3x + -5x = -8x (15 + -8x + x2) = 0 Solving 15 + -8x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (3 + -1x)(5 + -1x) = 0Subproblem 1
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {3, 5}
| 3z=4z | | =2x+3x+4x^2 | | 10x-12x-8=1 | | -7(m-1)=11(2m-2) | | 3t+7=t-1 | | -j/6=6 | | 5-3k+8k=-1+6k | | 63-6x=-15x | | 12x^2-23x-9=0 | | -0.23x+0.2(x-2)=-0.33(1-x) | | -414=-8(-8r+3)-6 | | 2(6t-4)=176t-t+4 | | w/3+3=6 | | -4.9=y+7.9 | | 5x-12=-2x^2 | | 0.07w+0.06(140-w)=90 | | -2n+n=-1+n+7+6 | | =8xy+2x | | 10x^2+48x-10=0 | | -4x=18-7x | | 35b-334=75 | | -5/8+x=1/3 | | x^3y-2xy^2+x^2y^3=0 | | 12m+60= | | -22x=-60 | | -4x=-6x-6 | | 7+5(f+2)= | | 7x^2+59x-36=0 | | 5x=3(2x-4) | | 36=25+49-14y+y^2 | | 4-11x=-48 | | 1-3a-8a=-8a-8 |